PD-L1 CAR effector cells induce self-amplifying cytotoxic effects against target cells - Leszek Pączek; Radoslaw Zagozdzon; Karl-Johan Malmberg; Malgorzata Bajor; Agnieszka Graczyk-Jarzynka; Katsiaryna Marhelava; Anna Burdzinska; Angelika Muchowicz; Agnieszka Goral; Andriy Zhylko; Karolina Soroczynska; Kuba Retecki; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors and chimeric antigen receptor (CAR)-based therapies have transformed cancer treatment. Recently, combining these approaches into a strategy of PD-L1-targeted CAR has been proposed to target PD-L1high tumors. Our study provides new information on the efficacy of such an approach against PD-L1low targets.Methods New atezolizumab-based PD-L1-targeted CAR was generated and introduced into T, NK, or NK-92 cells. Breast cancer MDA-MB-231 and MCF-7 cell lines or non-malignant cells (HEK293T, HMEC, MCF-10A, or BM-MSC) were used as targets to assess the reactivity or cytotoxic activity of the PD-L1–CAR-bearing immune effector cells. Stimulation with IFNγ or with supernatants from activated CAR T cells were used to induce upregulation of PD-L1 molecule expression on the target cells. HER2–CAR T cells were used for combination with PD-L1–CAR T cells against MCF-7 cells.Results PD-L1–CAR effector cells responded vigorously with degranulation and cytokine production to PD-L1high MDA-MB-231 cells, but not to PD-L1low MCF-7 cells. However, in long-term killing assays, both MDA-MB-231 and MCF-7 cells were eliminated by the PD-L1–CAR cells, although with a delay in the case of PD-L1low MCF-7 cells. Notably, the coculture of MCF-7 cells with activated PD-L1–CAR cells led to bystander induction of PD-L1 expression on MCF-7 cells and to the unique self-amplifying effect of the PD-L1–CAR cells. Accordingly, PD-L1–CAR T cells were active not only against MDA-MD-231 and MCF-7-PD-L1 but also against MCF-7-pLVX cells in tumor xenograft models. Importantly, we have also observed potent cytotoxic effects of PD-L1–CAR cells against non-malignant MCF-10A, HMEC, and BM-MSC cells, but not against HEK293T cells that initially did not express PD-L1 and were unresponsive to the stimulation . Finally, we have observed that HER-2–CAR T cells stimulate PD-L1 expression on MCF-7 cells and therefore accelerate the functionality of PD-L1–CAR T cells when used in combination.Conclusions In summary, our studies show that CAR-effector cells trigger the expression of PD-L1 on target cells, which in case of PD-L1–CAR results in the unique self-amplification phenomenon. This self-amplifying effect could be responsible for the enhanced cytotoxicity of PD-L1–CAR T cells against both malignant and non-malignant cells and implies extensive caution in introducing PD-L1–CAR strategy into clinical studies.